Association of occlusal support with type 2 diabetes: A community-based study - Da, Dongxin; Ge, Suyu; Zhang, Hao; Zeng, Xiaoli; Jiang, Yiwei; Yu, Jin; Wang, Huning; Wu, Wanqing; Xiao, Zhenxu; Liang, Xiaoniu; Ding, Ding; Zhang, Ying (Frontiers in Endocrinology, 2022)
Occlusal support was proved to be associated with type 2 diabetes. Our aim was to investigate the association between the Eichner index and the prevalence of type 2 diabetes. We included 715 participants with oral health examinations in the Shanghai Aging Study. The occlusal support status was determined by the number of functional occlusal support areas and Eichner index classifications. Those with fasting plasma glucose ≥126 mg/dL and/or hemoglobin A1c ≥6.5% and/or current medications for type 2 diabetes with relevant medical history were diagnosed with type 2 diabetes. Multiple logistic regression models were used to analyze the relationship between occlusal support status and type 2 diabetes. The average age of 715 participants was 73.74 ± 6.49 years old. There were 84 diabetics with 1.71 occlusal supporting areas on average. Seven hundred and fifteen participants were divided into 3 groups according to Eichner classifications: Eichner group A with 4 occlusal functional areas, Eichner group B with 1-3 occlusal functional areas or 0 area with anterior occlusal contact, and Eichner group C with no functional occlusal contact. Blood glucose level was significantly lower in participants of Eichner group A compared to those in group B or C. The ordinal logistic regression showed more occlusal supporting areas were significantly associated with less type 2 diabetes cases with an Odds Ratio(OR) of 0.253(95%CI 0.108-0.594) after adjusting covariates. Participants in Eichner group A had a significantly much lower OR of 0.078 for type 2 diabetes (95%CI 0.009-0.694) compared to those in Eichner group C after adjustment. The number of functional occlusal support areas might be inversely related to the blood glucose level and the prevalence of type 2 diabetes.